Increasing Utilization of Multiparametric Magnetic Resonance Imaging in Prostate Cancer Active Surveillance - Fam, Mina M.; Yabes, Jonathan G.; Macleod, Liam C.; Bandari, Jathin; Turner, Robert M.; Lopa, Samia H.; Furlan, Alessandro; Filson, Christopher P.; Davies, Benjamin J.; Jacobs, Bruce L. (Urology (Ridgewood, N.J.), 2019)
To characterize the use of multiparametric magnetic resonance imaging (mpMRI) in male Medicare beneficiaries electing active surveillance for prostate cancer. mpMRI has emerged as a tool that may improve risk-stratification and decrease repeated biopsies in men electing active surveillance. However, the extent to which mpMRI has been implemented in active surveillance has not been established. Using Surveillance, Epidemiology, and End Results registry data linked to Medicare claims data, we identified men with localized prostate cancer diagnosed between 2008 and 2013 and managed with active surveillance. We classified men into 2 treatment groups: active surveillance without mpMRI and active surveillance with mpMRI. We then fit a multivariable logistic regression models to examine changing mpMRI utilization over time, and factors associated with the receipt of mpMRI. We identified 9467 men on active surveillance. Of these, 8178 (86%) did not receive mpMRI and 1289 (14%) received mpMRI. The likelihood of receiving mpMRI over the entire study period increased by 3.7% (P = .004). On multivariable logistic regression, patients who were younger, white, had lower comorbidity burden, lived in the northeast and west, had higher incomes and lived in more urban areas had greater odds of receiving mpMRI (all P < .05). From 2008 to 2013, use of mpMRI in active surveillance increased gradually but significantly. Receipt of mpMRI among men on surveillance for prostate cancer varied significantly across demographic, geographic, and socioeconomic strata. Going forward, studies should investigate causes for this variation and define ideal strategies for equitable, cost-effective dissemination of mpMRI technology.